Social constructs, late recognition and decision making for managing fast breathing in children. (November 2020) - Agyei-Baffour, Peter; Ansong, Daniel; Osei, Francis Adjei; Appiah, Seth Christopher Yaw; Kwarteng, Sandra Owusu; Nyanor, Isaac; Bonney, Joseph; Enimil, Anthony; Odai Laryea, Dennis; Dapaah, Jonathan Mensah; Mensah, Nicholas; Osei-Peprah, Ida; et al.
Abstract: Purpose: Acute Respiratory Infection (ARI) is one of the topmost childhood killers ahead of diarrhoea and malnutrition in children. This exploratory qualitative study sought to examine the influence of maternal social constructs on the recognition and care seeking for fast breathing in children to inform the development of an intervention aimed at addressing fast breathing and acute respiratory infection related illness among children in Ghana. Method: Focus group discussions with 23 mothers with children aged 6 weeks – 12 weeks old was conducted. The study used an abbreviated grounded theory and thus the full iterative cycle was not performed during the interview and data analysis. Results: Fast breathing is locally called 'oteeso' (difficulty in breathing), and 'mframa-ko-ne-mu' (air has entered the child). Evil spirit, heredity, and exposure to windy weather were mentioned as the causes. Herbs and herbal preparations are perceived to be more effective in managing fast breathing. Mothers have varying construction of causes, presentation and treatment options for fast breathing, and these have implications in control and prevention. Conclusion: Understanding the local construction of illness beliefs is key to designing interventions aimed at empowering mothers to seek early care for their children on respiratory related illness.